The infrared view of dust and molecules around V4334 Sgr (Sakurai’s object): a 20-yr retrospective - Evans, Aneurin; Gehrz, R. D.; Woodward, C. E.; Banerjee, D. P. K.; Geballe, T. R.; Clayton, G. C.; Sarre, P. J.; Starrfield, S.; Hinkle, K.; Joyce, R. R.; Lykou, Foteini; Helton, L. A.; et al. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. We present an analysis of the evolution of circumstellar dust and molecules in the environment of the very late thermal pulse object V4334 Sgr (Sakur